A study of prescription pattern of the pharmacotherapy of patients of hypertension at a tertiary care hospital, Aurangabad,Maharashtra, India - Chandra, Shruti; Ubale, Amol; Bhosle, Deepak; Jayabhaye, Deepali; Kaur, Sukhmeen (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The overall prevalence for hypertension in India was estimated to be 29.8%. Patient’s optimal adherence with antihypertensive drug therapy is essential for preventing serious complications with hypertension over the long term. Therefore, the present study was undertaken to evaluate the prescription pattern of the drugs prescribed to hypertensive patients. Methods: Present study was a prospective cross sectional observational study carried out in the outpatient of department of general medicine of MGM Hospital, a tertiary care teaching hospital, in Aurangabad. Prescriptions of 120 diagnosed hypertensive patients were analysed. Data was recorded as mean±standard deviation. Results: The mean age of the patients was 57.13±10.94 years with range 18-80 years. 82.5 % (99) of patients were male and 17.5% (21) of patients were female. Mean duration of hypertension was 3.97±2.55. Most of the patients 57 (47.5%) were on Mono therapy significantly higher than dual therapy, triple therapy and poly therapy, 39 (32.5%), 15 (12.5%), 9 (7.5%) respectively. Calcium channel blocker was the frequently used class of drug for monotherapy (20%). Polytherapy was seen in 7.5% patient. Among 120 patients’ only 37 patients were reported ADR. Maximum no of ADRs were reported from patients receiving ACE inhibitor. Conclusions: This type of studies gives the base line idea of prescription pattern and ADRs of antihypertensive drugs. These help to design policy for rational use of drugs and motivation of physician for rational use of drugs.